2018
DOI: 10.1021/acsami.8b12746
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening of MOF Adsorbents and Membranes for H2 Purification and CO2 Capture

Abstract: Metal organic frameworks (MOFs) have emerged as great adsorbent and membrane candidates for separation of CO2/H2 mixtures. The main challenge is the existence of thousands of MOFs, which requires computational screening methods to identify the best materials prior to experimental efforts. In this study, we performed high-throughput computational screening of MOFs to examine their adsorbent and membrane performances for CO2/H2 separation. Grand canonical Monte Carlo (GCMC) and molecular dynamics (MD) simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
146
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(153 citation statements)
references
References 80 publications
7
146
0
Order By: Relevance
“…We previously showed that MOFs with high APSs generally suffer from low R %. 55 Figure S2a shows that most COFs (244 out of 288) have R % > 85%, but those with high APSs (>100 mol/kg) have a low R % under PSA conditions. On the other hand, Figure S2b shows that all COFs have R % > 85% as the lowest R % was computed as 95% under PTSA conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that MOFs with high APSs generally suffer from low R %. 55 Figure S2a shows that most COFs (244 out of 288) have R % > 85%, but those with high APSs (>100 mol/kg) have a low R % under PSA conditions. On the other hand, Figure S2b shows that all COFs have R % > 85% as the lowest R % was computed as 95% under PTSA conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that many COFs have better/similar performances than/to zeolites and hMOFs under PSA conditions, whereas MOFs generally have higher selectivities than COFs. 55 , 68 , 76 , 77 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 Grand canonical Monte Carlo (GCMC) simulations were performed for CO 2 /H 2 :40/60 mixture in 358 400 hMOFs and CO 2 /H 2 selectivities up to 300 and CO 2 working capacities up to 35 mol/kg were reported at 40 bar, 313 K. 27 These studies focused on hypothetical MOF structures, however performing molecular simulations on experimentally synthesized, readily available MOF structures is also important since there are already >88 000 existing MOFs. 28 531 real MOFs were screened and the top MOF was identified to have CO 2 working capacity of 6.0 mol/kg and CO 2 /H 2 selectivity of 83 for CO 2 /H 2 separation at 20 bar, 313 K. 26 Our group 29 recently screened 3857 experimentally synthesized MOFs obtained from the Cambridge Structural Database (CSD) and identified the top MOF adsorbents and membranes outperforming zeolites and polymers due to their high CO 2 /H 2 selectivities. Many more MOFs have been deposited into the CSD since then and computation-ready MOF database has been updated.…”
Section: Introductionmentioning
confidence: 99%
“…Many highthroughput computational screening studies used either of the databases to investigate the gas storage and/or gas separation potentials of MOF materials. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Simon et al 27 recently provided an excellent review on molecular simulations of MOFs and discussed some shortcomings of computation-ready MOF databases. For example, the method used for solvent removal from MOFs could be too aggressive so that (i) the structural integrity of some MOFs without solvents may become questionable or (ii) the MOF could relax into a different form after the solvent removal or (iii) performing automatic solventremoval on large numbers of MOFs can lead to chemically inaccurate structures by accidentally removing an essential part such as the ligand or CBIs of the framework.…”
Section: Introductionmentioning
confidence: 99%